2014
DOI: 10.1177/0269881114525674
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based pharmacological treatment of anxiety disorders, post-traumatic stress disorder and obsessive-compulsive disorder: A revision of the 2005 guidelines from the British Association for Psychopharmacology

Abstract: This revision of the 2005 British Association for Psychopharmacology guidelines for the evidence-based pharmacological treatment of anxiety disorders provides an update on key steps in diagnosis and clinical management, including recognition, acute treatment, longer-term treatment, combination treatment, and further approaches for patients who have not responded to first-line interventions. A consensus meeting involving international experts in anxiety disorders reviewed the main subject areas and considered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
499
2
21

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 570 publications
(523 citation statements)
references
References 474 publications
1
499
2
21
Order By: Relevance
“…Positive interactions represent additive or synergistic treatment effects and this can be potentially postulated for depression, anxiety, pain and migraine prophylaxis, but evidence-based data are limited. For example, pregabalin (PGB) is currently licensed for the treatment of generalised anxiety disorder and a recent study suggested a synergistic effects between antidepressants and PGB (37). Evidence-based data on augmentation strategies in neuropathic pain or migraine are limited although it is reasonable to hypothesise that the combined AED-antidepressant treatment could be favourable.…”
Section: Pharmacodynamic Interactions Between Antiepileptic and Antidmentioning
confidence: 99%
“…Positive interactions represent additive or synergistic treatment effects and this can be potentially postulated for depression, anxiety, pain and migraine prophylaxis, but evidence-based data are limited. For example, pregabalin (PGB) is currently licensed for the treatment of generalised anxiety disorder and a recent study suggested a synergistic effects between antidepressants and PGB (37). Evidence-based data on augmentation strategies in neuropathic pain or migraine are limited although it is reasonable to hypothesise that the combined AED-antidepressant treatment could be favourable.…”
Section: Pharmacodynamic Interactions Between Antiepileptic and Antidmentioning
confidence: 99%
“…Once the diagnosis has been explained to the patient, it is often reasonable to give a hopeful prognosis, outline the available treatments and negotiate a treatment package. Table 2) have been shown to be effective against the symptoms of panic disorder 13,14 and clinical studies have demonstrated high rates of efficacy -up to 80 per cent in some trials using drugs originally developed for depression (antidepressants). Among antidepressants, citalopram, escitalopram, paroxetine, sertraline and certain formulations of venlafaxine are licensed specifically for panic disorder.…”
Section: Treatment Of Panic Disordermentioning
confidence: 99%
“…Numerous double-blind randomised trials have demonstrated significantly higher rates of response or remission on active drug compared with placebo, despite panic disorder being typically associated with relatively high rates of placebo response. These trials, which will be discussed in the following paragraphs, are summarised in the British Association for Psychopharmacology guidelines for the evidence-based pharmacological treatment of anxiety disorders, post-traumatic stress disorder and obsessive-compulsive disorder 13 and described in greater detail in the Canadian clinical practice guidelines for the management of anxiety, post-traumatic stress and obsessive-compulsive disorders. 14 The main classes with evidence of efficacy are drugs that augment the function of serotonin (and sometimes noradrenaline) through reuptake blockade and drugs acting as positive allosteric modulators at GABA A receptor (benzodiazepines).…”
Section: Treatment Of Panic Disordermentioning
confidence: 99%
“…Zbog toge postoji preporuka je da se pacijentima sa generalizovanim anksioznim poremećajem za početak lečenja odredi terapija koja je pokazala efikasnost, a nema neželjena dejstva koja mogu da kompromituju tretman [5,6]. Pored toga, treba da se obrati pažnja na eventualno postojanje komorbidih oboljenja (pre svega depresije), ali i na praktične aspekte -kao što su iskustva sa terapijom, dostupnost terapije i lekara za buduće kontrole, ekonomske mogućnosti pacijenta, preference samog pacijenta i slično.…”
Section: Uvodunclassified
“…Što se tiče farmakoterapije, na osnovu kliničkog iskustva i na osnovu rezultata kliničkih studija, a na bazi potvrđene efikasnosti i najbenignijeg profila neže-ljenih dejstava, preporuka je da se pacijenti sa generalizovanim anksioznim poremećajem tretiraju nekim lekom iz grupe SSRI antidepresiva (citalopram, escitalopram, fluoksetin, paroksetin, sertralin), nekim lekom iz grupe iz grupe SNRI antidepresiva (duloksetin ili venlafaksin) ili pregabalinom, ukoliko ne postoje simptomi komorbidne depresije [5,6,7].…”
Section: Uvodunclassified